Physicochemical and community profiles of bacterial ecology in palm oil mill effluent final discharge and polluted river water - Sharuddin, Siti Suhailah (2017)
Palm oil industry is one of the major pillars of Malaysia economy. However, concurrent with the high production of palm oil, an enormous volume of palm oil mill effluent (POME) is being generated every year. Studies have shown that the discharging of treated POME into the river caused alterations of the natural properties of the receiving river, which consequently may also affect the biological balance of the ecosystem as a whole. In this study, a detailed evaluation of the impact of the treated POME final discharge on the bacterial communities with regards to their structural and functional status is discussed. The nucleic acid double staining assay based on flow cytometry was used to monitor the response of bacterial community functional status in terms of their total concentration, viability, and nucleic acid content, while the integration of PCR-denaturing gradient gel electrophoresis (DGGE) method and Illumina MiSeq approach, aided by advanced bioinformatics analysis have been used in analysing the bacterial community structures. The findings demonstrated a significant difference of bacterial community present in the upstream and downstream part, whereby the total cell concentration showed an increment in the downstream part of river water by 9.3 x 105 to 2.6 x 107 cells mL-1. It was also shown that the upstream part of the river was dominated by non-viable bacteria ranging from 44% to 75%, while the pattern was strongly shifted towards high percentage of viable bacteria in the downstream part of the river. The shift of low nucleic acid to high nucleic acid cells was also recorded, with the increment ranging from 17% to 36%, hence, suggesting the transformation of dormant to active cells due to the induction by POME final discharge which corresponded with the significant changes of the physicochemical properties. The discharged of POME also caused the reduction of diversity level in the downstream part of the river compared to the upstream part with the values of 9.277±0.521 and 9.869±0.776, respectively. The findings also demonstrated the shift of bacterial community composition in the downstream part of the river with the remarkable increment of Chromatiaceae and Alcaligenaceae by 35-fold and 4-fold, respectively. Hence, Chromatiaceae and Alcaligenaceae are proposed as the potential candidates for the indicator bacteria, which can be used to complement the physicochemical monitoring in assessing the river water pollution due to POME final discharge. More importantly, a sustainable palm oil industry can be developed with a reliable and accurate assessment method in strengthening the POME pollution management. To our knowledge, this is the first study on the effect of POME final discharge on bacterial community dynamics in the effluent receiving river.